PENGARUH VARIABEL MAKRO EKONOMI TERHADAP PENGHIMPUNAN DANA ZAKAT, INFAQ, DAN SEDEKAH (ZIS) DI INDONESIA TAHUN 2018-2022 - Almeyda, Devia; Rusgianto, Sulistya (Jurnal Ekonomika dan Bisnis Islam, 2023)
Zakat has an effect on the nation's aggregate demand, which can boost economic growth and lower the number of people living in poverty. Reduce the obstacles that may limit the ability for ZIS fund collection in order to enhance the potential for zakat revenue and combat poverty. To ascertain the impact of these elements on the volume of zakat, infaq, and sadaqah (ZIS) funds collected in Indonesia, this study will look at the effect of population, industrial production index, domestic investment, gross domestic product, exchange rate, and inflation in 2018-2022. The results showed that simultaneously, all macroeconomic variables affect the collection of ZIS funds. While partially, only the gross domestic product variable has an influence on the collection of ZIS funds in Indonesia.